Access to pedestal pressure relevant to burning plasmas on the high magnetic field tokamak Alcator C-Mod. (27th September 2018) - Hughes, J.W.; Snyder, P.B.; Reinke, M.L.; LaBombard, B.; Mordijck, S.; Scott, S.; Tolman, E.; Baek, S.G.; Golfinopoulos, T.; Granetz, R.S.; Greenwald, M.; Hubbard, A.E.; et al.
Abstract: Experiments on the Alcator C-Mod tokamak have utilized reactor-relevant magnetic fields to sustain substantially higher pedestal pressure than in other devices and allow close approach to the ITER H-mode baseline target pedestal pressure of 90 kPa. The EPED model, which couples the physics of transport driven by kinetic ballooning modes and MHD instabilities arising from peeling-ballooning modes, predicts the pressure profile at the onset of edge-localized modes (ELMs), and yields to lowest order a critical- β N like behavior for the pedestal: ( for fixed edge q ). C-Mod routinely accesses edge plasma pressure in excess of 30 kPa, often by using a high-density ( ) approach to high confinement, taking advantage of a regime known as enhanced D-alpha (EDA) H-mode. In the EDA H-mode, plasma transport regulates both the pedestal profiles and the core impurity content, thus holding the pedestal stationary at just below the peeling-ballooning stability boundary. This stationary ELM-suppressed regime has approached the maximum pedestal predicted by EPED at these densities: 60 kPa. This in turn gives rise to volume-averaged core plasma pressure in excess of 0.2 MPa, a world record value for a magnetic fusion device. Another approach to achieving high pressure utilizes a pedestal limited by current-driven modes at low collisionality, in which pressure increases with density and which allows access to a higher EPED solution, termed 'super-H'. C-Mod experiments at reduced density ( ) and strong plasma shaping ( ) accessed this regime, producing pedestals with pressures up to 80 kPa (approximately 90% of the ITER target) and temperatures of nearly 2 keV. In a number of these hot H-modes, we observe strong edge instabilities at low toroidal mode number ( n   =  1) when pedestal pressure approaches predicted values from EPED, showing that current-driven MHD modes can serve as a limit on the pedestal in a metal-walled tokamak at high pressure and low collisionality.